Pengaruh Kualitas Pelayanan Dan Citra Rumah Sakit Terhadap Kepuasan Pasien Rawat Jalan Di Rsud Banyuasin Sumatera Selatan - Dwi Ris Andriyanto; A. Rum Tajang; Ansar Taufik (STIE AMKOP, 2022)
Abstract The purpose of this study was to determine and analyze the effect of service quality and hospital image on outpatient satisfaction at Banyuasin Hospital. The type of research in this study is associative. The sampling technique in this study was accidental sampling. Data collection methods in this study were questionnaires, and documentation studies. Methods of data analysis using descriptive analysis methods and multiple linear regression analysis. The results showed that the variables of service quality and hospital image simultaneously had a positive and significant effect on outpatient satisfaction at the Banyuasin General Hospital. Adjusted R Square value of 0.352 means 35.2% indicates that the variable patient satisfaction can be explained by the quality of service and hospital image. While the remaining 64.8% can be explained by other factors not examined in this study. Keywords: Service Quality, Image and Satisfaction